Effects of first radioiodine ablation on functions of salivary glands in patients with differentiated thyroid cancer. Issue 25 (June 2017) - Upadhyaya, Arun; Meng, Zhaowei; Wang, Peng; Zhang, Guizhi; Jia, Qiang; Tan, Jian; Li, Xue; Hu, Tianpeng; Liu, Na; Zhou, Pingping; Wang, Sen; Liu, Xiaoxia; et al.
Abstract : Abstract: The aim of this study was to evaluate the effects of the first radioactive iodine ( 131 I) therapy on functions of salivary glands in patients with differentiated thyroid carcinoma (DTC). There were 36 consented patients with DTC enrolled in this study, who received 3.7 GBq (100mCi) 131 I for ablation after total thyroidectomy. Salivary gland function was assessed using salivary gland scintigraphy in two phases, one 4 hours before and the other 6 months after 131 I therapy (both under thyrotropin stimulation condition). Quantitative parameters including uptake fraction (UF), uptake index (UI), excretion fraction (EF), and excretion ratio (ER) were measured and compared. Blood parameters were also compared. Associations between sex and outcome of the first 131 I therapy as well as individual salivary gland function were measured. Wilcoxon Signed Rank Sum test and χ 2 test were used for statistical analysis. When compared between pre-ablation and post-ablation, UF of bilateral parotid and submandibular glands were significantly increased (all P  < .01). UI of both submandibular glands were significantly increased ( P  < .05). This seemingly increased uptake function after the first 131 I therapy was actually compensatory mechanism of salivary gland, which indicated a possible intermediate state after radiation. But salivary glands' secretory function had not changed significantly except for left submandibular gland; we demonstrated that only left submandibular gland showed significantly decreased ER ( P  < .05). Thyroglobulin and thyroglobulin antibody significantly decreased after 131 I therapy ( P  < .05). There were no sex differences on therapeutic outcome and salivary gland dysfunctions after the first 131 I therapy. Salivary gland of both males and females could be affected by 131 I therapy. The first 131 I ablative therapy may impair the salivary uptake and secretory function of patients with DTC. There was no association between sex and salivary gland dysfunction.